2021
DOI: 10.1089/dia.2020.0667
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Real-Time Continuous Glucose Monitoring in Pregnancy

Abstract: In recent years, continuous glucose monitoring (CGM) has become increasingly available with the introduction of devices that are specifically approved for use during pregnancy. Evidence in the form of randomized-controlled trials and cohort studies continues to build support for the use of CGM during pregnancy to improve measures of maternal glycemia as well as obstetric and neonatal outcomes. Based on data from the CGM in pregnant women with type 1 diabetes (CONCEPTT) trial alongside a Swedish cohort study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…However, decreasing blood glucose values with insulin is associated with a high risk of maternal hypoglycemia, including severe episodes ( 87 ). Continuous glucose monitoring during pregnancy improves maternal glycemia and pregnancy outcomes, and is now recommended in pregnant women with type 1 diabetes ( 88 ). Moreover, it has been suggested that closed-loop and sensor-augmented pump insulin delivery could be efficient to lower blood glucose levels without increasing the risk of severe hypoglycemia in pregnant women ( 89 ).…”
Section: In Several Areas There Could Be Opportunities To Improve The...mentioning
confidence: 99%
“…However, decreasing blood glucose values with insulin is associated with a high risk of maternal hypoglycemia, including severe episodes ( 87 ). Continuous glucose monitoring during pregnancy improves maternal glycemia and pregnancy outcomes, and is now recommended in pregnant women with type 1 diabetes ( 88 ). Moreover, it has been suggested that closed-loop and sensor-augmented pump insulin delivery could be efficient to lower blood glucose levels without increasing the risk of severe hypoglycemia in pregnant women ( 89 ).…”
Section: In Several Areas There Could Be Opportunities To Improve The...mentioning
confidence: 99%
“…For pregnant women with type 1 diabetes, uptake of CGM technology improves neonatal outcomes, 38 but CGM remains to be widely tested for pregnant individuals with type 2 diabetes. In the future, HbA 1c may become redundant with increasing use of CGM in pregnancy 39 . It is possible that gestational weight gain, as opposed to weight assessed at a single time point, such as at delivery in the current study, could affect the association between HbA 1c and perinatal outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…The culmination of this evidence has resulted in the recommendation to offer isCGM to all pregnant women with PGDM who are unable or unwilling to use rtCGM ( 76 ).…”
Section: Technologiesmentioning
confidence: 99%